Efek Minyak Zaitun terhadap Kadar Glukosa Darah Puasa dan Kadar Growth Differentiation Factor-15 (GDF-15) pada Tikus Model Diabetes - Darmawansyih; Risma Irnawati; Fairuz Salsabilah Rum; Asri Saleh (Universitas Islam Negeri Alauddin Makassar, 2025)
Olive oil contains high antioxidants and has been widely studied for its effect on diabetes mellitus (DM). However, no previous research has examined the effect of olive oil on levels of Growth Differentiation Factor-15 (GDF-15), where levels increase in inflammatory conditions. The study aimed to examine the effects of olive oil on body weight, blood glucose levels and GDF-15 levels in type I DM and type II DM. It was an experimental research with a Pre and Post-Test Control Group Design approach using 12 Rattus novergicus divided into three groups: group (I) diabetes control, group II (DM I), and group III (DM II). The results showed significant changes in body weight in the Control and DM II groups before and after treatment (p= 0.028 and p= 0.018). There were significant differences in blood glucose levels in the Control, DM I and DM II groups (p= 0.002; 0.019; 0.034); GDF-15 levels had significant changes only in the DM II group (p= 0.016). The conclusion was that olive oil affects body weight and GDF-15 levels in DM II diabetic model rats and reduces blood glucose levels in diabetic model rats of DM I and DM II.